Radiocarbon and geologic evidence reveal Ilopango volcano as source of the colossal 'mystery' eruption of 539/40 CE. (15th October 2019) - Dull, Robert A.; Southon, John R.; Kutterolf, Steffen; Anchukaitis, Kevin J.; Freundt, Armin; Wahl, David B.; Sheets, Payson; Amaroli, Paul; Hernandez, Walter; Wiemann, Michael C.; Oppenheimer, Clive
Abstract: Ilopango volcano (El Salvador) erupted violently during the Maya Classic Period (250–900 CE) in a densely-populated and intensively-cultivated region of the southern Maya realm, causing regional abandonment of an area covering more than 20, 000 km 2 . However, neither the regional nor global impacts of the Tierra Blanca Joven (TBJ) eruption in Mesoamerica have been well appraised due to limitations in available volcanological, chronological, and archaeological observations. Here we present new evidence of the age, magnitude and sulfur release of the TBJ eruption, establishing it as one of the two hitherto unidentified volcanic triggers of a period of stratospheric aerosol loading that profoundly impacted Northern Hemisphere climate and society between circa 536 and 550 CE. Our chronology is derived from 100 new radiocarbon measurements performed on three subfossil tree trunks enveloped in proximal TBJ pyroclastic deposits. We also reassess the eruption magnitude using terrestrial (El Salvador, Guatemala, Honduras) and near-shore marine TBJ tephra deposit thickness measurements. Together, our new constraints on the age, eruption size (43.6 km 3 Dense Rock Equivalent of magma, magnitude = 7.0) and sulfur yield (∼9–90 Tg), along with Ilopango's latitude (13.7° N), squarely frame the TBJ as the major climate-forcing eruption of 539 or 540 CE identified in bipolar ice cores and sourced to the tropics. In addition to deepening appreciation of the TBJ eruption's impacts in Mesoamerica, linking it to the major Northern Hemisphere climatic downturn of the mid-6th century CE offers another piece in the puzzle of understanding Eurasian history of the period. Graphical abstract: Image 1 Highlights: Major eruption of Ilopango volcano, El Salvador occurred in the first half of the 6th century. Ilopango eruption is consistent with 'mystery' eruption of 540 CE that caused global cooling. Magnitude 7 event ranks as one of the 10 largest on Earth in past 7000 years. Impacts on the Maya of Central America were severe, including estimated 100, 000 + fatalities.